Orientation of Entrepreneurship and Innovation in Improving the Company's Performance through Business Strategy - Mukson Mukson; Syariefful Ikhwan; Slamet Bambang Riono (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
This research was conducted to know and develop and analyze the influence of entrepreneurial orientation and innovation on the company's performance with business strategy as a variable intervention. This research was conducted on small and medium enterprises located in Brebes Regency. The type of research is explanatory research by using questionnaires as a tool or research instrument, the questionnaire are close-ended with five alternative answer options and measured using the Likert scale. The number of samples used in this study amounted to 95 SMEs in Brebes District using purposive sampling techniques. Data analysis uses Structural Equation Modeling with the help of Partial Least Square 2.0. The result of this study is that the orientation of entrepreneurship, innovation, and business strategy directly positively and significantly affects the performance of the company; Entrepreneurial orientation directly positively and significantly affects business strategy. Innovation does not have a direct positive and significant effect on business strategy; entrepreneurial orientation does not positively and significantly affect the company's performance through business strategy, and innovation directly affects the company's performance through business strategy.